COGNITIVE APPROACH TO THE LITOTES SEMANTICS STUDIES IN THE ENGLISH BLOGS - O. N. Pavlenkova (Вестник Кемеровского государственного университета, 2013)
The main postulates of the cognitive science are summarized in the article. The semantics and stylistics of the litotes constructions are analyzed through the cognitive approach. The author also characterizes the blog as one of the new types of mass media discourse.